2002
DOI: 10.1088/1367-2630/4/1/334
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of turbulence measurements and simulations of the low-temperature plasma in the torsatron TJ-K

Abstract: Abstract. A toroidal low-temperature plasma is used for comparative turbulence studies. Measurements are carried out with Langmuir probe arrays in the entire plasma cross section. The data are closely compared with drift-Alfvén turbulence simulations. Although the parameters in a low-temperature plasma are very different from those in fusion plasmas, the dimensionless parameters governing the drift-wave physics are comparable. Hence this study can also give insight into high-temperature plasma turbulence. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Moreover, negative values of the total turbulent transport corresponding to inward transport is repeatedly observed for some microseconds. As it was shown in former works, plasmas in TJ-K are fully dominated by electrostatic drift-wave turbulence [27,28,29]. Turbulent diffusivities in TJ-K estimated from a random walk model using measured radial correlation lengths and the lifetime of turbulent structures turn out to be about two orders of magnitude larger than neoclassical ones [30].…”
mentioning
confidence: 67%
“…Moreover, negative values of the total turbulent transport corresponding to inward transport is repeatedly observed for some microseconds. As it was shown in former works, plasmas in TJ-K are fully dominated by electrostatic drift-wave turbulence [27,28,29]. Turbulent diffusivities in TJ-K estimated from a random walk model using measured radial correlation lengths and the lifetime of turbulent structures turn out to be about two orders of magnitude larger than neoclassical ones [30].…”
mentioning
confidence: 67%
“…10). Since it is known that TJ-K plasmas are dominated by drift-wave turbulence [35], it is expected [2] that turbulent structures propagate into the direction of the electron-diamagnetic drift…”
Section: D-dynamics Of Drift-wave Turbulencementioning
confidence: 99%
“…In these studies, complex wave patterns in poloidal direction have been observed (see also reports from toroidal plasma experiments, e.g., [11][12][13][14]). These advancements highlight the need to measure fluctuations at multiple spatial positions simultaneously.…”
Section: Introductionmentioning
confidence: 98%